Advances in Gastrointestinal and Liver Disease: From Physiological Mechanisms to Clinical Practice (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Advancements in the management of gastrointestinal and hepatic diseases have been possible through a better understanding of their underlying mechanisms. For instance, the development of direct-acting antivirals has been achieved through improved knowledge of HCV infection. The incidences of peptic disease and stomach cancer have been reduced through efforts to decrease H. pylori infection, increased use of proton-pump inhibitors, and greater accessibility to gastroscopies. Targeted therapies such as anti-TNF, anti-IL12/23, and anti-JAK have been developed based on an understanding of the inflammatory pathways involved in inflammatory bowel disease. Finally, increased knowledge of the microbiota will lead to novel clinical applications beyond gut-related diseases.